Compostos derivados de taurina, processo de preparação e composições contendo ditos derivados - Vizioli, Ednir de Oliveira; Chin, Chung Man [UNESP]; Menegon, Renato Farina; Blau, Lorena; Santos, Jean Leandro dos [UNESP]; Longo, Maria do Carmo [UNESP] (Instituto Nacional de Propriedade Industrial (INPI), 2014)
The present invention relates to compounds derived from taurine with non-steroidal anti inflammatory activity. In a first embodiment, the present invention relates to compounds derived from taurine, in which taurine is bound directly by means of an amide bond or through an spacing group, to a compound selected from the group of non-steroidal anti inflammatory compounds, cited as derived from taurine presenting the Formula (I): in which R means the component with non-steroidal anti inflammatory activity. In a second embodiment, the invention provides a process for obtaining the compounds of Formula (I) by reaction of taurine with a compound belonging to the group of non-steroidal anti inflammatory (NSAIs), in order to obtain a compound derived from taurine by direct bond or through a spacing group of the taurine to the NSAI. The invention also relates to the pharmaceutical compositions comprising at least one compound derived from taurine presenting non-steroidal anti inflammatory activity.
Novel compounds derived from taurine, process of their preparation and pharmaceutical compositions containing these
Processo: PI0800951-1
Processo: WO2009124371
Número de publicação: US2014057959 (A1)
Número de aplicação: US201314035690